PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA KELAS VI SD STELLA MARIS JAMBI - Charles Darwin; Indriyani; Ugi Nugraha; Urip Sulistiyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Project based Learning learning model is a learning approach centered on a challenging and authentic project or task. In this model, students are given the opportunity to apply their knowledge and skills in real contexts, thus motivating them to learn more actively and engaged. The purpose of this study is to improve the English speaking ability of grade VI students of SD Stella Maris Jambi by applying a project-based learning model. This research is a classroom action research (PTK), this class action research (PTK) is carried out in two cycles with the aim of improving students' English speaking skills. The data collection tools used in this study are tests and observations. The subjects studied were teachers and students of grade VI of SD Stella Maris Jambi. The results of the study show that by using the project-based learning model to improve students' English speaking skills, each cycle has increased significantly. The change that was previously not good became better. Successively based on cycle one and cycle two. Of the 30 students, as many as 7 students (23.33%) did not complete because the scores obtained had not reached the expected KKM, which was 70. So that the percentage of student completeness obtained is 68%. Meanwhile, the Classical Completeness Standard, classically considered to have completed learning if it reaches 80% of the number of students who achieve a minimum absorption capacity of 70. Meanwhile, in the second cycle, the average score data was 86.67. Of the 30 students, as many as 6 students (23%) did not complete because the scores obtained had not reached the expected KKM, which was 70. So that the percentage of student completeness obtained was 86.67%. Meanwhile, the Classical Completeness Standard, classically considered to have completed learning if it reaches 80% of the number of students who achieve a minimum absorption capacity of 70. The application of the Picture and Picture learning model can ultimately improve students' English speaking skills at SD Stella Maris Jambi.